Modeling of dielectric relaxation for lossy materials at microwave frequencies using polynomial approaches - You, Kok Yeow (Penerbit UTM, 2012)
This paper reviews the dielectric modeling techniques and features of various dielectric models. In fact, many of the dielectric models have a polynomial characteristic, thus polynomial fitting is proposed in order to estimate the parameters in the dielectric model based on measured data. The coefficients of the polynomial equation were optimized with the measured data using HP 85070 B dielectric probe. Finally, the parameters in the dielectric models can be easily determined, based on the estimated polynomial coefficients. The parameters of the dielectric model were successfully estimated and compared with parameter values in the literature.